Vine Shoots and Grape Stalks as Carbon Sources for Hydrogen Evolution Reaction Electrocatalyst Supports - Cardoso, J. A. S. B.; Sljukic, B.; Erdem, M.; Sequeira, C. A. C.; Santos, D. M. F. (Mdpi, 2018)
Activated bio-based carbons produced from vine shoots (VSAC) and grape stalks (GSAC), which have larger surface area and total pore volume than most of the commercially available activated carbons, are used as supports for palladium nanoparticles (Pd NPs). The prepared materials are characterised by elemental analysis, N-2-sorption, X-ray diffraction, scanning electron microscopy with energy dispersive X-ray spectroscopy, and transmission electron microscopy analysis and are then assessed as potential cathodes for the hydrogen evolution reaction (HER) in alkaline media. The electrocatalysts' performance for HER is evaluated from cathodic polarisation curves at different temperatures and compared to that of Vulcan XC72-supported Pd NPs. Additional chronoamperometry studies helped to assess the electrocatalysts' activity stability. The novel VSAC-supported Pd electrocatalyst exhibits good HER activity in terms of high current density at low overpotentials, leading to the best performance.
Keywords: palladium nanoparticles; bio-based activated carbon; alkaline water electrolysis; hydrogen evolution reaction